Childhood Diarrheal Diseases and Associated Factors in the Rural Community of Dejen District, Northwest Ethiopia - Getu, Demeke; Gedefaw, Molla; Abebe, Nurilign (American Scientific Research Journal for Engineering, Technology, and Sciences, 2013)
Diarrheal diseases are among the three most important causes of morbidity, and mortality in low income countries including Ethiopia. Lack of sanitation facilities is a serious health risk and obliges people to practice open defecation, thereby increasing the risk of disease transmission. These problems are clear at Dejen district where childhood diarrheal disease is the top cause of morbidity among under five children. The aim of this study was to assess prevalence of childhood diarrheal diseases and associated factors in the rural community of Dejen district, northwest Ethiopia, 2014. In this paper; a community-based cross-sectional study was conducted. Five of the 21 rural kebeles in the district was selected randomly, finally 710 households were chosen by systematic random sampling using existing list of all households as a sampling frame. Data was collected using pre-tested WHO core questionnaire that was designed to explore factors related to diarrhea. Data enter and analysis was carried out using SPSS version 20. The level of association was dealt using confidence interval and odds ratio. This study conducted among 710 participants with response rate of 96.4% shows that, the prevalence of diarrhea was 23.8%. Tube well water source (AOR: 2.59,95% CI (169,3.95)), throwing away disposal of feces (AOR: 1.58,95% CI (1.10,2.26)), mother’s used hand washing with practice only water (AOR: 1.61,95% CI (1.04,2.84)) and having not supplemented with vitamin A (AOR: 1.92,95% CI(1.35,2.74)) were significantly associated with diarrhea. the prevalence of childhood diarrhea is high at Dejen district. Tube well source of water, throwing away disposal of feces, poor hand washing practice of the mother and lack of vitamin A supplementation were significantly associated with childhood diarrheal disease. The District and Zonal water office should increasing access of piped water in rural areas. The District and Zonal health office should improve awareness of the community on hand washing practice and on proper utilization of latrine to dispose excreta should be given a concern and Vitamin Supplementation to every child in the district should be strengthened.